Cotidiano e trabalho: experiências negras e escravas em Taquara (1856 – 1888) - Freitas, Ubiratã Ferreira (2019)
The present thesis inscribed in the Frontier, Political and Society Research line, has as its theme "Daily and Labor: Black and Slave Experiences in Taquara (1856-1888)", the following is about the participation and presence of African and Afro-Brazilian in the region of Vale do Rio dos Sinos – Paranhana, where the former Fazenda Mundo Novo was located, whose work and exploitation of enslaved individuals had great importance for local development and production for a wide trade that was established from farmers, livestock farmers, traders and atafoneiros, favoring the economic development of the region. The analysis of this economic phenomenon allowed us to perceive adverse aspects of the society that developed. The thesis also presents the dynamics of socioeconomic composition that verified the invisibility of the black population in the region, such as social exclusion and also its trajectory as an element of resistance, since its presence manifests itself in construction and contribution formation of the current municipality of Taquara - RS, with these individuals having an important share at work and in various segments of the Mundo Novo Farm society, increasingly perpetrating the possibilities of a mixed society, but at the same time within the context of colonization and social formation. In view of the studies that have been produced over the past few years, the contribution of the Black African population has been highlighted since its arrival in Brazil. Thus, starting from this premise, Afro-Brazilians had the association of African cultural values present, which are part of the current national culture and their dismay is clear in every way. For such considerations we analyzed a documental body of primary source composed of post mortem inventory, crime process, ecclesiastical books of baptism and marriage that enabled the importance of deconstruction of black invisibility, in the composition of the society of the municipality of Taquara-RS, and together with German colonization, becomes of paramount importance for the recognition of African roots in Rio Grande do Sul to value these workers. Thus, the black presence, from 1856 until 1888, favored the development of this thesis, legitimizing the African and Afro-Brazilian presence in the lands of the former Fazenda Mundo Novo.